2015
DOI: 10.7717/peerj.1008
|View full text |Cite
|
Sign up to set email alerts
|

Niche distribution and influence of environmental parameters in marine microbial communities: a systematic review

Abstract: Associations between microorganisms occur extensively throughout Earth’s oceans. Understanding how microbial communities are assembled and how the presence or absence of species is related to that of others are central goals of microbial ecology. Here, we investigate co-occurrence associations between marine prokaryotes by combining 180 new and publicly available metagenomic datasets from different oceans in a large-scale meta-analysis. A co-occurrence network was created by calculating correlation scores betw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
28
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(32 citation statements)
references
References 62 publications
4
28
0
Order By: Relevance
“…Identification of functional niches and complex microbial interactions in the rumen microbiome was possible using co-abundance network analysis. This approach was successfully applied for the study of the gut microbiome and other ecosystems (Coutinho et al, 2015;Xiao et al, 2017;Bauer et al, 2018).…”
Section: Functional Niches In the Rumen Microbiomementioning
confidence: 99%
“…Identification of functional niches and complex microbial interactions in the rumen microbiome was possible using co-abundance network analysis. This approach was successfully applied for the study of the gut microbiome and other ecosystems (Coutinho et al, 2015;Xiao et al, 2017;Bauer et al, 2018).…”
Section: Functional Niches In the Rumen Microbiomementioning
confidence: 99%
“…This deduction is in agreement with the study of Coutinho et al, (2015) who, based on 180 marine prokaryote metagenomic datasets, suggested that the abundance of the bacteria is positively or negatively correlated with the available nutrients. For example, bacteria that were more abundant in eutrophic waters were found less so in oligotrophic waters (Coutinho et al, 2015).…”
Section: Effect Of Microalgae On Bacterial Compositionsupporting
confidence: 92%
“…The co-existence of microalgae and bacteria in an aquaculture system indicates that they can be mutualistic and, through ecological resource partitioning, they help to stabilize the ecosystem. Meanwhile, a RAS is an eutrophic system, which from an ecological macro-scale point of view, represents a segment of an ecological niche (Coutinho et al, 2015). Microalgae and bacteria share the role of ammonia removal in a RAS.…”
mentioning
confidence: 99%
“…The new genus encompasses marine strains of Cyanobacteria formerly known as Synechococcus, closely related to the genus Prochlorococcus. Parasynechococcus is a dominant member of marine microbial communities and is among the most important contributors of global primary productivity (Flombaum et al 2013;Coutinho et al 2015). These organisms have developed diverse strategies for nutrient uptake (Palenik et al 2003), production of secondary metabolites (Micallef et al 2015) and light harvesting and utilization (Six et al 2007a, b).…”
Section: Introductionmentioning
confidence: 98%